Airlines’ Corporate Growth and Environmental Conservation: Evidence from Global Carriers and Forwarders - Tsujimoto, Masao (International Journal of Energy Economics and Policy, 2024)
This study explores how global airlines can achieve growth and environmental conservation using transport, financial performance, and carbon dioxide (CO₂) emissions data before, during, and after the COVID-19 pandemic from 2019 to 2022 with manually collected data for 38 leading international airlines. First, the regression analyses identify a clear range of turning points that airlines should consider in terms of Scopes 1 and 2 CO₂ emissions per employee and cargo ton-kilometers per employee (cargo ton-kilometers (CTK)/EMP) considering the environmental Kuznets Curve (EKC) hypothesis. Second, the deciding factors, including fundamental efforts by the airlines themselves, result from the interaction of three points, which have been encouraged and promoted in the airline industry in recent years. (1) Tighter emissions controls for air transport, (2) investors’ emphasis on environment, society, and governance (ESG), and (3) assessments and guidelines from ratings agencies and economic and environmental organizations. Third, increasing CTK/EMP to verified thresholds and taking an ESG-oriented approach can contribute to airlines’ combined achievement of growth and environmental conservation and related data will expand academic and policy-related research.